Detection of mRNA Expression and Copy Number Variations Within the Goat FecB Gene Associated With Litter Size - Bi, Yi; Feng, Weijie; Kang, Yuxin; Wang, Ke; Yang, Yuta; Qu, Lei; Chen, Hong; Lan, Xianyong; Pan, Chuanying (Frontiers in Veterinary Science, 2021)
The Booroola fecundity (FecB) gene, as the first major fecundity gene identified in Booroola sheep, has attracted careful attention. So far, previous research have uncovered the FecB mutation (Q249R) as the main mutation by virtue of which sheep exhibits multiple lambing phenomena. This mutation is now being intensively studied and widely used. However, such effect of the FecB mutation has not been applied to goats, and similar types of the FecB gene in goats still need to be studied. Thus, the current study attempted to verify potential mutations in the goat FecB gene as well as investigate their functions related to fecundity. First, FecB expression was investigated in six different goat tissues, and we found that FecB expression was highest in the mammary gland, followed by the ovary. Next, the influence of the FecB gene was analyzed from a new perspective, where five potential copy number variations (CNVs) (CNV1–5) within the FecB gene were identified for the first time, and then their effects on litter size were measured. Our results point out that CNV3 (P = 3.44E-4) and CNV5 (P = 0.034) could significantly influence the litter size of goats. Identically, the combination genotype of CNV3 and CNV5 which consisted of their dominant genotypes was also significantly associated with goat litter size (P = 7.80E-5). Hence, CNV3 and CNV5 could serve as potential DNA molecular markers applied to DNA editing and DNA microarray. Additionally, the abovementioned study has laid a theoretical foundation for the detection of potential fertility-related quantitative trait loci within the goat FecB gene.